Mesh complications and failure rates after transvaginal mesh repair compared with abdominal or laparoscopic sacrocolpopexy and to native tissue repair in treating apical prolapse. (February 2017) - Dandolu, Vani; Akiyama, Megumi; Allenback, Gayle; Pathak, Prathamesh
Abstract Objective Our objective was to quantitate the extent of complications and failure rate for apical prolapse repair with transvaginal mesh (TVM) use versus sacrocolpopexy over a minimum of 2 years of follow-up. Methods Truven CCAE and Medicare Supplemental databases 2008–2013 were used for analysis. Patients with apical prolapse repair via transvaginal mesh (TVMR), abdominal sacrocolpopexy (ASCP), laparoscopic sacrocolpopexy (LSCP), or native tissue repair (NTR) and continuously enrolled for years were in the study cohort. Surgical failures were identified by reoperation for any prolapse or subsequent use of pessary. SAS® 9.3 was used for analysis. Results Mesh removal/revision was reported highest in TVMR (5.1 %), followed by LSCP (1.7 %) and ASCP (1.2 %). In those with concomitant sling, combined rates for mesh/sling revision were high, at 9.0 % in TVMR + sling, 5.6 % in ASCP + sling, and 4.5 % LSCP + sling. Sling-alone cases reported a 3.5 % revision rate. Pelvic pain (16.4–22.7 %) and dyspareunia (5.6–7.5 %) were high in all three approaches for apical prolapse repairs. Reoperation for apical prolapse was more common for TVMR (2.9 %) compared with NTR (2.3 %) [odds ratio (OR) 1.27; confidence interval (CI) 1.1–1.47;p 0.002]. Both ASCP and LSCP were superior to NTR (ASCP 1.5 %, OR 0.63, CI 0.46–0.86;p 0.003) and LSCP 1.8 % (OR 0.79, CI 0.62-1.01;p 0.07). Overall prolapse recurrence, as indicated by any compartment surgery for prolapse and/or pessary use, was also noted highest in TVMR (5.9 % OR 1.23, CI 1.11–1.36;p <0.0001). Laparoscopic sacrocolpopexies were slightly superior at 4.0 % overall recurrence (OR 0.83, CI 0.7–0.98);p 0.03). Failure of incontinence surgery was higher when the initial procedure combined prolapse and sling surgery (1.97 %) versus sling alone (1.6 %). Conclusions Reoperation for apical prolapse is more common with TVMR than with sacrocolpopexies and NTR. Incontinence procedures are more likely to fail when performed along with prolapse repair than when performed alone. When mesh is used for repair, mesh revision is highest with TVMR and lowest with ASCP.